The Students’ Confession Toward Teacher Techniques in Teaching English - Aswin Abbas; Faiz Naufal Asrul (Ethical Lingua: Journal of Language Teaching and Literature, 2020)
Confession contributes to the effectiveness and motivation both students and teachers. It invites the students’ participation in determining the good technique for the best teacher. This research deals with students’ confession toward teacher technique in teaching based on gender. The objective of the research is try to elaborate how is the students’ confession on different gender, male and female in teaching. This research analyzed qualitatively where the subject takes from Senior High School 3 Palopo, 40 samples take which is confessing 10 male and 13 female teachers. After doing an interview, found that there are some confessions toward Gender teacher technique in teaching, they are both male and female get positive confessions, Male teachers get 36 confessions with good managing confessing (9) is the highest where correlated to the topic is a few or only 2 stdents confessed. Female teachers get 39 confessions with good managing confessing about 7 students assumed it and it is the highest. Furthermore, motivated confession only 2 confessing, and the last is female teachers get higher confession than male.